Estimation of Modulus of Resilience of Hot Mix Asphalt by Utilizing the Indirect Tensile Strength Test Data of the Bituminous Mixes - Prasad, Piyush (My University, 2022)
The value of modulus of resilience is a prime variable, which is being used by the pavement engineer and pavement designer in the design of pavement as well as in the evaluation of pavement performance subjected to hammering effect due to dynamic traffic loading. There are many empirical methods developed by the expert researchers to determine the resilient modulus based upon the factor which is affecting it mostly or the parameters which is showing good dependency. As a result, the dependence of resilient modulus on indirect tensile strength (ITS) test data has been a topic of interest. This research study aims to provide approach to validate the analysed ITS test result of bituminous mix with the laboratory resilient modulus values thereby reducing the need for testing on expensive equipment and trained personnel. Therefore, in order to reach at the value of both indirect tensile strength as well as the resilient modulus, it would be required to prepare marshall specimen on which the performance test need to be carried. Different grade of specimen were prepared consists of bituminous concrete grade 1 (BC-1), bituminous concrete grade 2 (BC- 2), dense bituminous concrete grade 1 (DBM-1), dense bituminous grade 2 (DBM-2), stone matrix asphalt with nominal maximum aggregate size of 13 mm (SMA NMA 13 mm) and stone matrix asphalt with nominal maximum aggregate size of 19 mm (SMA NMA 19 mm). The binders used for these grade mix includes bitumen of viscosity grade 40 (VG 40), polymer modified bitumen grade 40 (PMB 40) and crumb rubber modified bitumen grade 60 (CRMB 60). The various materials used in the mix design for specimen preparation were tested to check their characterstics to meet the specified limit and standard. The gradation has been fixed as per the MoRT&H specification. Trial and error method is adopted to fix the mix gradation for different grade and to further minimize the effect of gradation, blending is such that for each mix it is near to center line. The marshall specimen were prepared at an obtained optimum bitumen content for different types of mix grade. Indirect tensile strength (ITS) test was conducted on each samples were analysed and further a trial has been conducted to arrive at the modulus value from the ITS data analysis. It has been seen that the obtained modulus from the ITS test data will be nearly same as the resilient modulus value obtained from the laboratory testing using the universal testing machine carried out as per the ASTM D 4123 code.
Keywords: Modulus; Resilience; Pavement Performance; emperical